Importance of Supplier Quality and Supplier Relationship Quality in Supply Chain - Sheren Aurelia Widjaja; Bambang Darmawan (Universitas Pendidikan Indonesia, 2022)
The lack of awareness of companies to choose quality suppliers often leads to changing suppliers. In addition, another thing that contributes to the change of suppliers is the lack of awareness of the company to manage good relationships with suppliers. The impact of changing suppliers is that there are changes in the goods or services offered to customers, such as quality, specifications, and others. Furthermore, this will affect customer satisfaction and if the quality decreases, it can result in losses for the company. The purpose of this article is to determine the urgency of supplier quality and supplier relationship quality. The method used in data collection is Literature Review (LR). Supplier quality and supplier relationship quality play an important role in the supply chain. Then one of the important factors that must be developed to improve the quality of the relationship is the communication factor.